WORKPLACE HAPPINESS: : an analysis from the perspective of workers in the city of São Carlos - Lima, Nathalia Tassi; Viveiros, Leticia Vitória; Rodrigues, Lilian Segnini (Revista Interface Tecnológica, 2023)
The pursuit of happiness among people has been gaining attention not only in organizations, but also in the general context of all countries. As human beings spend a good part of their time at work, which is a central space in their lives, happiness at work becomes an important factor that contributes to the generation of positive feelings. The objective of this article is to identify the factors that determine happiness and mainly unhappiness of employees in the work environment in various companies in the city of São Carlos-SP. For this purpose, an online questionnaire consisting of 20 questions, 19 of which were closed-ended and 1 open-ended, was applied and sent to people working in different areas. A total of 111 responses were collected, the results were analyzed and it was concluded that people are generally "moderately happy" in their work. This is an indicator of a positive and healthy work environment, which can lead to greater job satisfaction and motivation. However, negative and indecisive responses must be considered, as they may point to areas that need improvement.